Association between Long-Term Exposure to Fine Particulate Matter and Asthma Incidence among School-Aged Children - Lim, Hyun Mook; Ryoo, Seung Woo; Hong, Yun Chul; Kim, Soon Tae; Lim, Youn Hee; Lee, Dong Wook (Atmosphere, 2022)
Studies on the correlation of long-term PM2.5 exposure with childhood-onset asthma are limited to western countries. We aimed to study the association between long-term PM2.5 exposure and childhood-onset asthma in South Korea, which has higher ambient PM2.5 levels than western countries. We constructed a retrospective cohort of children aged 6–14 years living in seven metropolitan cities using the National Health Insurance service in South Korea from 2011 to 2016. Children who made a hospital visit with asthma from 2008 to 2010 were excluded. A child was diagnosed with asthma incidence if he or she visited the hospital three times or more with a primary diagnostic code of asthma. A time-varying Cox regression model was constructed to investigate the association of long-term district-level PM2.5 exposure with asthma incidence. Of the 1,425,638 children evaluated, 52,133 showed asthma incidence, with an incidence rate of 6.9 cases/1000 person-years. A 10 µg/m3 increase in the 48-month moving average PM2.5 exposure was associated with an elevated risk of asthma incidence, with a hazard ratio of 1.075 (95% confidence interval: 1.024–1.126), and this association was robust for different PM2.5 exposure levels (12-, 36-, and 60-month moving average). In this study, long-term exposure to PM2.5 was associated with asthma incidence in school-aged children in South Korea. Policies to reduce environmental PM2.5 levels and protect children from PM2.5 are necessary to prevent childhood-onset asthma.
Keywords: Asthma; Child; Cohort studies; Fine particulate matter; Long term exposure; Moving averages; Particulate Matter; PM 2.5; South Korea; Western countries; asthma; children; cohort study; long-term exposure; particulate matter